Contraceptive knowledge, attitude and practices among Catholic and non-Catholic couples in Ibadan, Nigeria. (2014)
Employing the neo-Malthusian and Voluntary Social Action Theories, this paper argues that irrespective of denomination Christians in Ibadan perceive family planning as an essential mechanism for achieving fertility reduction and moderate family size. Data were collected through questionnaire survey, Focus Group Discussions (FGDs), In-depth Interviews (IDIs) and Key Informant Interviews (KIIs). Results indicate that 98 percent of the respondents claimed to be knowledgeable about contraceptives; while 67 percent of respondents who are Catholics approved of contraception, only 42 percent of them actually used these contraceptives. Condom was mostly used by the respondents generally; cost/non-affordability and side effects are the main reasons why respondents may not use contraceptives even when they approve of it. Church leaders in both groups stressed the importance of family planning for achieving a moderate family size. Prioritizing advocacy to religious groups will go a long way in ensuring positive attitudinal and behavioural change towards adoption of context specific family planning strategies.